The Role of Automation in Modern Healthcare: Innovations and Impact. - Shashank Agnihotri; Mohit Kumar; Ketan Anand (International Journal of Electrical and Communication Engineering Technology, 2024)
Automation technology encompasses a broad array of systems and tools designed to perform tasks with minimal human intervention, thereby increasing efficiency, reducing errors, and enhancing productivity. This study explores the core components of automation technology, including sensors, actuators, controllers, and software, and examines their applications across various industries. In manufacturing, automation leads to significant improvements in production speed and precision. In healthcare, it enhances patient care and operational efficiency. In transportation, automation reduces traffic congestion and improves safety through autonomous vehicles and intelligent traffic management systems. Home automation improves energy efficiency and provides enhanced security and convenience. Despite the numerous benefits, automation technology also presents challenges such as high initial costs, integration complexity, and potential job displacement. Future trends, driven by advancements in artificial intelligence, machine learning, and the Internet of Things, promise to further revolutionize automation technology, making systems more intelligent and adaptable. This study highlights the transformative impact of automation on diverse sectors and underscores the importance of addressing its challenges to maximize its benefits.
Keywords: Actuator; Automation; CCD RTD; ITS; sensors